2020
DOI: 10.24276/rrecien2358-3088.2020.10.29.40-47
|View full text |Cite
|
Sign up to set email alerts
|

Estratégias nas instituições de saúde para reduzir estresse na enfermagem

Abstract: O objetivo deste estudo foi identificar as principais estratégias utilizadas pelas instituições de saúde para diminuir o estresse entre a equipe de enfermagem. Trata-se de uma revisão integrativa composta por 14 artigos que apresentam estratégias de redução do stress voltada a equipe de enfermagem em serviços de saúde que foram estratificados nos eixos temáticos: Educação Permanente, Gestão, Relacionamento e Práticas Complementares. Com os altos índices de estresse que acometem as equipes de instituições de sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
0
3
0
7
Order By: Relevance
“…As for strategies to cope with BS, a recent Brazilian integrative review showed three different possible axes of actions taken by health institutions with the aim of reducing stress among the nursing staff: management and education, dialogue and reflections of work, and spaces for biopsychosocial and physical well-being. It is necessary that the development and implementation of strategies are carried out considering the suggestion of the professionals involved in the processes, so that they feel valued and so that it is possible to make everyday life more productive (32) .…”
Section: Discussionmentioning
confidence: 99%
“…As for strategies to cope with BS, a recent Brazilian integrative review showed three different possible axes of actions taken by health institutions with the aim of reducing stress among the nursing staff: management and education, dialogue and reflections of work, and spaces for biopsychosocial and physical well-being. It is necessary that the development and implementation of strategies are carried out considering the suggestion of the professionals involved in the processes, so that they feel valued and so that it is possible to make everyday life more productive (32) .…”
Section: Discussionmentioning
confidence: 99%
“…Este estudo ressalta a importância de um acolhimento, com escuta qualificada, para os profissionais, seus pares e a chefia discutirem sobre os problemas, objetivando reflexões que ajudem e transformem o ambiente de trabalho, diminuindo os níveis de estresse dessas pessoas (23)(24) .…”
Section: Principais Resultadosunclassified
“…Estes dados corroboram com a literatura, que traz o excesso de trabalho como favorecedor de cansaço e redutor do autocuidado e lazer e, em decorrência disto, aumenta os níveis de estresse, com resultados negativos na qualidade do trabalho (23) . Portanto, é imprescindível que as instituições de saúde não proporcionem aos seus profissionais longas jornadas de trabalho, principalmente em momentos de pandemias.…”
Section: Principais Resultadosunclassified
“…Estratégias nas instituições de saúde para reduzir estresse na enfermagem. (Calil & Francisco, 2020) Identificar as principais estratégias utilizadas pelas instituições de saúde para diminuir o estresse entre a equipe de enfermagem.…”
Section: Describe Micropractices For Burnout Prevention and Emotional Well-beingunclassified